Optimal HE-PWM inverter switching patterns using differential evolution algorithm - Muhammad Ikram, Mohd Rashid; Hiendro, Ayong; Anwari, Makbul (IEEE, 2012)
This paper presents a differential evolution (DE) algorithm to solve the optimum switching angles problem in the harmonic elimination pulse width modulation (HE-PWM) inverter. Reformulated equations for two-level schemes are proposed to satisfy the DE algorithm. Optimum solutions are found for odd value of switching angles (odd N) case within all range of modulation index M. The DE algorithm needs a relative small amount of generations to reach accurate solutions with appropriate control parameters. The comparison of some common variants in the DE shows that all variants may generate the same precision results by using their best specific crossover rate and mutation factor values. MATLAB/Simulink simulation results confirm that the solutions obtained by the proposed technique can be applied to eliminate the entire undesired specific harmonics as expected by the proposed formulation.